The historical background of Catalan separatism: The case of Occitania - Sasor, Rozalia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this study is to discuss the originality of the Catalan literature at its beginnings in relation to the poetry of the Occitan troubadours, and to explain why some Catalans today do not feel connected to the Castilian heritage. The paper presents the Occitan-Catalan political and cultural relations in the time between 993 and 1213, with particular emphasis on the 12th century when the Great Occitan War took place.
Keywords: House of Barcelona; Catalan Occitan campaign; Occitan-Catalan cultural circle; Counts of Barcelona; Great Occitan War